Effect of Carrier Transport on Thermal Distribution in Laser Diode - M. I. Azawe (College of Education for Pure Sciences, 2009)
ABSTRAC: A comprehensive numerical model to simulate self-heating effects of laser diode under continuous-wave operation is presented. The model is self-consistently accounts for the close interaction between optical, electrical, and thermal processes in the laser diode. Electro-thermal simulation offers the possibility of examining the effects on device performance of structure. Thermal profiles and time-dependent heat diffusion is presented in this investigation. Current injection modified the Peltier coefficient at interfaces; and gives rise to thermoelectric cooling at the active region and on the device parameters. Lattice temperatures, included in the rate equations were found to shift the frequency of the resonant dominant mode of the laser diode emission. 3D thermal plot of the thermal distribution was obtained in order to assess the heat diffusion as carrier-dependent for the laser diode.